Positive electrode active material and lithium ion secondary battery

By integrating specific elements into the O2 type structure of positive electrode active materials, the battery achieves improved cycle characteristics during high-speed charging and discharging, addressing the limitations of conventional materials.

JP7619254B2Active Publication Date: 2025-01-22TOYOTA JIDOSHA KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021205432
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-17
Publication Date
2025-01-22
Estimated Expiration
2041-12-17

AI Technical Summary

Technical Problem

Conventional positive electrode active materials with an O2 type structure have suboptimal cycle characteristics during high-speed charging and discharging.

Method used

Incorporating specific elements such as Mn, Ni, Co, and M (where M is B, Mg, Al, K, Ca, Ti, Cr, Ga, Zr, Nb, or Mo) into the O2 type structure, with a peak intensity ratio of X-ray photoelectron spectroscopy (XPS) peaks between 0.5 and 1.2, and maintaining a specific composition Li a Na b Mn x-p Ni y-q Co z-r M p+q+r O 2, where 0

Benefits of technology

The resulting lithium ion secondary battery exhibits enhanced cycle characteristics during high-speed charging and discharging, with improved performance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619254000004
    Figure 0007619254000004
  • Figure 0007619254000005
    Figure 0007619254000005
  • Figure 0007619254000006
    Figure 0007619254000006
Patent Text Reader

Abstract

To disclose a cathode active material having O2 type structure, and having an excellent cycle characteristic at high-speed charge and discharge.SOLUTION: A cathode active material having O2 type structure is disclosed, including as constituent elements, at least Li, at least one of Mn, Ni and Co, and M and O. The M is at least one of B, Mg, Al, K, Ca, Ti, Cr, Ga, Zr, Nb, and Mo.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application discloses a positive electrode active material and a lithium ion secondary battery. [Background technology]

[0002] A positive electrode active material having an O2 type structure is known. The positive electrode active material having an O2 type structure is stable even at high potential, so that charging and discharging in a high potential range can be utilized, and high energy density can be easily obtained. As disclosed in Patent Documents 1 and 2, the positive electrode active material having an O2 type structure can be obtained by substituting at least a part of Na of a Na compound having a P2 type structure with Li. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2021-068556 [Patent Document 2] Patent Publication No. 2021-068555 Summary of the Invention [Problem to be solved by the invention]

[0004] Conventional positive electrode active materials with an O2 structure have room for improvement in terms of cycle characteristics during high-rate charge and discharge. [Means for solving the problem]

[0005] As one of the means for solving the above problems, the present application provides: A positive electrode active material having an O2 type structure, Constituent elements include at least Li, at least one of Mn, Ni, and Co, M, and O; The M is at least one of B, Mg, Al, K, Ca, Ti, Cr, Ga, Zr, Nb, and Mo; positive electrode active material Disclose.

[0006] As one of the means for solving the above problems, the present application provides: A positive electrode active material having an O2 type structure, When the surface of the positive electrode active material is analyzed by X-ray photoelectron spectroscopy (XPS), the ratio I1 / I2 of the maximum peak intensity I1 of peak 1 present at 2 eV or less to the maximum peak intensity I2 of peak 2 present at more than 2 eV and 8 eV or less is 0.5 or more and 1.2 or less. positive electrode active material Disclose.

[0007] In the positive electrode active material of the present disclosure, the peak 2 may be present in the range from more than 2 eV to 6 eV or less.

[0008] The positive electrode active material of the present disclosure is Li a Na b Mn x-p Ni y-q Co z-r M p+q+r O2 (wherein the relationships 0≦a≦1, 0≦b≦0.05, x+y+z=1, and 0.05≦p+q+r≦0.14 are satisfied).

[0009] As one of the means for solving the above problems, the present application provides: A lithium ion secondary battery having a positive electrode, an electrolyte layer, and a negative electrode, The positive electrode comprises the positive electrode active material of the present disclosure; Lithium-ion secondary battery Disclose. Effect of the Invention

[0010] A lithium ion secondary battery having the positive electrode active material of the present disclosure has excellent cycle characteristics during high-rate charge and discharge. [Brief description of the drawings]

[0011] [Figure 1] 1 illustrates a schematic configuration of a lithium ion secondary battery. [Diagram 2]1 shows X-ray diffraction peaks of positive electrode active materials according to examples and comparative examples. [Diagram 3] 1 shows XPS spectra of positive electrode active materials according to examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] 1.Cathode active material Hereinafter, a first embodiment and a second embodiment of the positive electrode active material of the present disclosure will be illustrated.

[0013] 1.1 First embodiment The positive electrode active material according to the first embodiment has an O2 type structure. Here, the positive electrode active material according to the first embodiment contains, as constituent elements, at least Li, at least one of Mn, Ni, and Co, M, and O. The M is at least one of B, Mg, Al, K, Ca, Ti, Cr, Ga, Zr, Nb, and Mo.

[0014] 1.1.1 Crystal structure The positive electrode active material according to the first embodiment includes at least an O2 type structure (belonging to space group P63mc) as a crystal structure. The positive electrode active material according to the present disclosure may have an O2 type structure and may have a crystal structure other than the O2 type structure. Examples of crystal structures other than the O2 type structure include a T♯2 type structure (belonging to space group Cmca) formed when Li is deintercalated from an O2 type structure and an O6 type structure (belonging to space group R-3m, having a c-axis length of 2.5 nm or more and 3.5 nm or less, typically 2.9 nm or more and 3.0 nm or less, and different from the O3 type structure also belonging to space group R-3m). The positive electrode active material according to the first embodiment may have an O2 type structure as a main phase, or may have a crystal structure other than the O2 type structure as a main phase. The positive electrode active material according to the first embodiment may have a crystal structure as a main phase that changes depending on the charge / discharge state.

[0015] 1.1.2 Composition The positive electrode active material according to the first embodiment includes, as constituent elements, at least Li, at least one of Mn, Ni, and Co, M, and O. The positive electrode active material according to the first embodiment may include, as constituent elements, at least Li, at least one of Mn and Co, M, and O, or may include at least Li, Mn, Ni, M, and O, or may include at least Li, Co, M, and O, or may include at least Li, Mn, Ni, Co, M, and O. In addition, the positive electrode active material according to the first embodiment may release Li by charging, and the amount of Li may approach 0.

[0016] The positive electrode active material with the O2 type structure has the problem that valence localization easily occurs and the diffusion barrier is easily high. For example, Li 0.67 Mn x Ni y Co z Assuming a composition of O2, the O2 type structure can only be synthesized under the condition that charge neutrality occurs when Mn is +4, Ni is +2, and Co is +3, i.e., x+y+z=1 and 4x+2y+3z=3.33, or in the vicinity thereof. This indirectly indicates that valence localization is likely to occur in the O2 type structure. If valence localization causes the diffusion barrier to become high, this may adversely affect high-speed charge / discharge performance. For example, cycle characteristics may be easily deteriorated.

[0017] In order to achieve delocalization of valence in a system where valence localization is likely to occur, it is necessary to introduce a system in which electrons are likely to leave the atom and spread. As described above, transition metals typically used to form a positive electrode active material having an O2 type structure include Mn, Ni, and Co, but all of these ions have a 3d orbital as the outermost orbital, and the spread of electrons is small. In this regard, (1) it is considered that by introducing an ion having a larger spread of electrons than Mn, Ni, and Co (for example, an ion having a p orbital or s orbital as the outermost orbital) into a positive electrode active material having an O2 type structure, the spread of electrons can be increased, and delocalization of valence can be achieved. In addition, (2) the energy level of the outermost orbit must be at a level that contributes to charge and discharge as a positive electrode active material. As a result of intensive research, the present inventor has found the following element M as an additive element that satisfies both of the above (1) and (2).

[0018] The positive electrode active material according to the first embodiment includes at least one of B, Mg, Al, K, Ca, Ti, Cr, Ga, Zr, Nb, and Mo as the constituent element M. M is an element up to the fifth period of the periodic table. For elements in the sixth period or later of the periodic table, the ion radius is too large to be introduced into the O2 type structure, or the ion is unstable. When the positive electrode active material having the O2 type structure includes M as a constituent element, as described above, the valence is delocalized, the electrons are easily separated from the atoms and spread, the diffusion barrier is lowered, and the cycle characteristics during high-speed charge and discharge are improved. In particular, when M is at least one of Mg, Al, and Ga, and especially when M is at least one of Mg and Al, a higher effect can be expected. Among the elements M, Ti, Cr, Ga, Zr, Nb, and Mo can be expected to have a small effect on the capacity due to the change in the valence of M during charge and discharge, in addition to the above-mentioned delocalization effect of the valence. Among the elements M, Mg, Al and Ti are expected to have the above-mentioned valence delocalization effect and, due to their structural stabilization effect, to improve cycle characteristics during charge and discharge, including in the high potential region of 4.5 V or higher, and to suppress oxygen release and heat generation due to heating.

[0019] The positive electrode active material according to the first embodiment is Lia Na b Mn x-p Ni y-q Co z-r M p+q+r It may have a composition represented by O2. Here, the relationships 0 < a ≤ 1, 0 ≤ b ≤ 0.05, x + y + z = 1, and 0.05 ≤ p + q + r ≤ 0.14 are satisfied. When having such a composition, the O2-type structure is maintained, and the delocalization of valence is sufficiently achieved, making it easier to further improve the cycle characteristics during high-speed charge and discharge.

[0020] In the above composition, a may be greater than 0, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, or 0.6 or more, and may also be 1.0 or less, 0.9 or less, 0.8 or less, or 0.7 or less. In the above composition, b may be 0.05 or less, 0.04 or less, 0.03 or less, 0.02 or less, 0.01 or less, or 0. In the above composition, x may be 0 or more, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, or 0.5 or more, and may also be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, or 0.5 or less. In the above composition, y may be 0 or more, 0.1 or more, or 0.2 or more, and may also be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.3 or less, or 0.2 or less. In the above composition, z may be 0 or more, 0.1 or more, 0.2 or more, or 0.3 or more, and may also be 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, or 0.3 or less. The composition of O is approximately 2, but is not necessarily exactly 2.0 and is indefinite.

[0021] As described above, element M contributes to the delocalization of valence. Assuming that the effect of the delocalization of valence caused by element M extends to the third nearest transition metal, if p+q+r is 0.05 or more, the entire crystal structure can be covered in a state in which valence is delocalized. It is considered that the effect of the delocalization of valence actually extends to the first nearest transition metal, but the Li vacancies that exist as a result are also located around the second and third nearest transition metals, so the above assumption can be said to be reasonable. On the other hand, if p+q+r is too large, element M will be placed up to the first nearest transition metal site. Since the ionic radius of M is significantly different from that of the transition metal that should be placed at the transition metal site, there is a concern that the crystal structure will become unstable if M is contained excessively. By making p+q+r 0.14 or less, such problems can be easily avoided. p+q+r may be 0.06 or more, 0.07 or more, or 0.08 or more, or may be 0.13 or less, 0.12 or less, 0.11 or less, or 0.10 or less.

[0022] In the above composition, when the valence of M is +n, the relationship 3.0≦4(xp)+2(yq)+3(zr)+n(p+q+r)≦3.5 may be satisfied. This is intended to be a range in which the total valence of metals in the positive electrode active material is close to 3.33 (charge neutral when a is 0.67). As described later, a positive electrode active material having an O2 type structure is synthesized via a Na compound having a P2 type structure, and the charge neutrality occurs when the Na composition at this time is in the range of 0.5 to 1.0, which corresponds to the case where the above relationship is satisfied. Here, the upper limit value 1.0 for the Na composition is the maximum composition in the structure. Also, if the Na composition is below the lower limit value 0.5, it becomes difficult to maintain the P2 type structure.

[0023] The composition of the positive electrode active material can be determined, for example, by inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0024] 1.1.3 Other matters The shape of the positive electrode active material according to the first embodiment may be a general shape for a positive electrode active material of a battery. For example, the positive electrode active material may be particulate. The particles of the positive electrode active material may be solid particles, hollow particles, or particles having voids. The particles of the positive electrode active material may be primary particles, or secondary particles formed by agglomeration of a plurality of primary particles. The average particle diameter (D50) of the positive electrode active material may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less. The average particle diameter D50 in the present application is the particle diameter (median diameter) at an integrated value of 50% in a volume-based particle size distribution obtained by a laser diffraction / scattering method.

[0025] The positive electrode active material according to the first embodiment may satisfy the requirements for the ratio I1 / I2 which will be described in the following second embodiment.

[0026] 1.2 Second embodiment The positive electrode active material according to the second embodiment has an O2 type structure, as in the first embodiment. Here, when the surface of the positive electrode active material according to the second embodiment is analyzed by X-ray photoelectron spectroscopy (XPS), the ratio I1 / I2 of the maximum peak intensity I1 of peak 1 present at 2 eV or less and the maximum peak intensity I2 of peak 2 present at more than 2 eV and 8 eV or less is 0.5 or more and 1.2 or less. In addition, when a protective layer is present on the surface of the positive electrode active material, when the protective layer is removed by sputtering by more than twice the thickness of the protective layer, and the active material surface after the protective layer is removed is analyzed by XPS, the above ratio I1 / I2 is 0.5 or more and 1.2 or less.

[0027] 1.2.1 Crystal structure The crystal structure of the positive electrode active material according to the second embodiment may be the same as that of the first embodiment, as described above in detail.

[0028] 1.2.2 Composition The composition of the positive electrode active material according to the second embodiment is not particularly limited as long as it has the above crystal structure and the peak intensity ratio I1 / I2 in the XPS analysis satisfies the above conditions. The positive electrode active material having an O2-type structure may contain, for example, at least one of Li and Na, a transition metal element, and O as constituent elements, or may contain at least Li, a transition metal element, and O. Examples of the transition metal element include at least one element among Mn, Ni, and Co. In particular, when the constituent elements include at least Li, Mn, at least one of Ni and Co, and O, the performance as a positive electrode active material is more likely to be enhanced, especially when the constituent elements include at least Li, Mn, Ni, Co, and O.

[0029] In order to satisfy the above peak intensity ratio I1 / I2, the positive electrode active material according to the second embodiment may contain some constituent elements in addition to Li, Mn, Ni, Co, and O. For example, the above-described element M can be mentioned, but there may be elements other than element M that can achieve the peak intensity ratio I1 / I2.

[0030] The positive electrode active material according to the second embodiment may have the same composition as that of the first embodiment. That is, the positive electrode active material according to the second embodiment may have a composition represented by Li a Na b Mn x-p Ni y-q Co z-r M p+q+r O2, where the relationships 0 < a ≤ 1, 0 ≤ b ≤ 0.05, x + y + z = 1, and 0.05 ≤ p + q + r ≤ 0.14 are satisfied. The details of the composition of a, b, x, y, z, p, q, r, and O are as described above.

[0031] 1.2.3 Peak intensity ratio I1 / I2 When a positive electrode active material having an O2 type structure contains Li, a transition metal (Mn, Ni and / or Co), and O as constituent elements, and does not contain any other elements, in an XPS analysis, a peak 1 derived from the 3d electrons of the transition metal is observed near a binding energy of 1 to 2 eV, and a peak 2A derived from the 2p electrons of oxygen is observed near a binding energy of 6 to 8 eV. Here, the maximum intensity I1 of peak 1 and the maximum intensity I 2A Peak intensity ratio I1 / I 2A is greater than 1.4, that is, peak 1 becomes larger relative to peak 2A, and there is a large intensity difference between peak 1 and peak 2A (see the spectrum of Comparative Example 1 in FIG. 3). In addition, there is an energy difference of 4 eV or more between the top of peak 1 and the top of peak 2A.

[0032] In contrast, in the positive electrode active material according to the second embodiment, the ratio I1 / I2 of the maximum peak intensity I1 of peak 1 present at 2 eV or less to the maximum peak intensity I2 of peak 2 present at more than 2 eV and 8 eV or less is 0.5 or more and 1.2 or less. This means that in the O2 type structure, ions having a large spread of electrons with p orbitals or s orbitals as the outermost orbitals are introduced, and the peak 2A originating from the 2p electrons of oxygen near 6 to 8 eV and the peak 2B originating from the introduced ions are mixed to form a large peak 2. In addition, the peak 1 originating from the 3d electrons of the transition metal near the binding energy of 1 to 2 eV can also become small so as to be absorbed by the peak 2B originating from the introduced ions.

[0033] In this way, when the peak intensity ratio I1 / I2 is 0.5 or more and 1.2 or less while having an O2 type structure, it is considered that the valence is delocalized in the O2 type structure, the electrons are easily separated from the atoms and spread, the diffusion barrier is lowered, and the cycle characteristics during high-speed charge and discharge are improved. The peak intensity ratio I1 / I2 may be 0.8 or more and 1.1 or less.

[0034] The introduced ions having an s or p outermost orbit are wider than the peak derived from the d orbit of the transition metal. For example, the peak 2B derived from the introduced ion has a maximum width from the peak top to the peak bottom of about 5 eV, so if the peak 2B is in the vicinity of 6 eV, the band is applied to the valence band. In addition, since the introduced ion needs to contribute to charging and discharging not only in the high potential region but also in the entire region, it is preferable that the peak 2B is located at a position where the binding energy is lower than 6 eV. When the peak 2B derived from the introduced ion is located at a position lower than 6 eV, the peak 2, which is a mixed peak of the peak 2A derived from the 2p electrons of oxygen and the peak 2B derived from the introduced ion, appears at a position of 6 eV or less, that is, it appears shifted to the lower energy side than the original position of the peak 2A (see the spectra of Examples 1 and 2 in FIG. 3). In this regard, in the positive electrode active material according to the second embodiment, it is preferable that the peak 2 exists at more than 2 eV and not more than 6 eV. In this case, it is considered that the electrons are more likely to spread away from the atoms and the diffusion barrier is further lowered, and the cycle characteristics during high-speed charging and discharging are further improved.

[0035] 1.2.4 Other matters The shape of the positive electrode active material according to the second embodiment may be the same as that in the first embodiment.

[0036] 2. Positive electrode The technology of the present disclosure also has an aspect of a positive electrode including a positive electrode active material having the above-mentioned O2 type structure. That is, the positive electrode of the present disclosure includes at least one of the positive electrode active material according to the first embodiment and the positive electrode active material according to the second embodiment. As shown in FIG. 1, a positive electrode 10 according to one embodiment may include a positive electrode active material layer 11 and a positive electrode current collector 12, and in this case, the positive electrode active material layer 11 may include the above-mentioned positive electrode active material.

[0037] 2.1 Cathode active material layer The positive electrode active material layer 11 contains at least the positive electrode active material having the O2 type structure as the positive electrode active material, and may further contain an electrolyte, a conductive assistant, a binder, and the like. Furthermore, the positive electrode active material layer 11 may contain various other additives. The content of each of the positive electrode active material, electrolyte, conductive assistant, binder, and the like in the positive electrode active material layer 11 may be appropriately determined according to the target battery performance. For example, the content of the positive electrode active material may be 40 mass% or more, 50 mass% or more, or 60 mass% or more, and may be 100 mass% or less, or 90 mass% or less, assuming that the entire positive electrode active material layer 11 (total solid content) is 100 mass%. The shape of the positive electrode active material layer 11 is not particularly limited, and may be, for example, a sheet-like positive electrode active material layer 11 having a substantially flat surface. The thickness of the positive electrode active material layer 11 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.

[0038] 2.1.1 Cathode active material The positive electrode active material layer 11 may contain only the positive electrode active material having the O2 type structure as the positive electrode active material. Alternatively, the positive electrode active material layer 11 may contain, in addition to the positive electrode active material having the O2 type structure, a different type of positive electrode active material (another positive electrode active material). From the viewpoint of further enhancing the effect of the technology of the present disclosure, the content of the other positive electrode active material in the positive electrode active material layer 11 may be small. For example, the content of the positive electrode active material having the O2 type structure may be 50 mass% or more, 60 mass% or more, 70 mass% or more, 80 mass% or more, 90 mass% or more, 95 mass% or more, or 99 mass% or more, based on the total positive electrode active material contained in the positive electrode active material layer 11 being 100 mass%.

[0039] The surface of the positive electrode active material may be covered with a protective layer containing a lithium ion conductive oxide. That is, the positive electrode active material layer 11 may include a composite having the above-mentioned positive electrode active material and a protective layer provided on the surface thereof. This makes it easier to suppress the reaction between the positive electrode active material and a sulfide (for example, a sulfide solid electrolyte described later). Examples of lithium ion conductive oxides include Li3BO3, LiBO2, Li2CO3, LiAlO2, Li4SiO4, Li2SiO3, Li3PO4, Li2SO4, Li2TiO3, Li4Ti5O 12 , Li2Ti2O5, Li2ZrO3, LiNbO3, Li2MoO4, and Li2WO4. The coverage (area ratio) of the protective layer may be, for example, 70% or more, 80% or more, or 90% or more. The thickness of the protective layer may be, for example, 0.1 nm or more or 1 nm or more, and may be 100 nm or less, or 20 nm or less.

[0040] 2.1.2 Electrolytes The electrolyte that can be contained in the positive electrode active material layer 11 may be a solid electrolyte, a liquid electrolyte (electrolytic solution), or a combination thereof.

[0041] The solid electrolyte may be any known solid electrolyte for lithium ion secondary batteries. The solid electrolyte may be an inorganic solid electrolyte or an organic polymer electrolyte. In particular, inorganic solid electrolytes are excellent in ion conductivity and heat resistance. Examples of inorganic solid electrolytes include lithium lanthanum zirconate, LiPON, Li 1+X Al X Ge 2-XExamples of the oxide solid electrolyte include (PO4)3, Li-SiO-based glass, and Li-Al-SO-based glass; and sulfide solid electrolytes such as Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Si2S-P2S5, Li2S-P2S5-LiI-LiBr, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, and Li2S-P2S5-GeS2. In particular, sulfide solid electrolytes, particularly sulfide solid electrolytes containing at least Li, S, and P as constituent elements, have high performance. The solid electrolyte may be amorphous or crystalline. The solid electrolyte may be, for example, particulate. Only one type of solid electrolyte may be used alone, or two or more types may be used in combination.

[0042] The electrolyte may contain, for example, lithium ions as carrier ions. The electrolyte may be an aqueous electrolyte or a non-aqueous electrolyte. The composition of the electrolyte may be the same as that of the electrolyte of a lithium ion secondary battery. For example, the electrolyte may be a carbonate-based solvent in which a lithium salt is dissolved at a predetermined concentration. Examples of the carbonate-based solvent include fluoroethylene carbonate (FEC), ethylene carbonate (EC), and dimethyl carbonate (DMC). Examples of the lithium salt include LiPF6.

[0043] 2.1.3 Conductive additives Examples of the conductive assistant that may be included in the positive electrode active material layer 11 include carbon materials such as vapor grown carbon fiber (VGCF), acetylene black (AB), ketjen black (KB), carbon nanotubes (CNT), and carbon nanofibers (CNF); and metal materials such as nickel, aluminum, and stainless steel. The conductive assistant may be, for example, particulate or fibrous, and the size is not particularly limited. Only one type of conductive assistant may be used alone, or two or more types may be used in combination.

[0044] 2.1.4 Binders Examples of binders that can be included in the positive electrode active material layer 11 include butadiene rubber (BR)-based binders, butylene rubber (IIR)-based binders, acrylate butadiene rubber (ABR)-based binders, styrene butadiene rubber (SBR)-based binders, polyvinylidene fluoride (PVdF)-based binders, polytetrafluoroethylene (PTFE)-based binders, polyimide (PI)-based binders, etc. Only one type of binder may be used alone, or two or more types may be used in combination.

[0045] 2.2 Positive electrode current collector As shown in FIG. 1, the positive electrode 10 may include a positive electrode collector 12 in contact with the positive electrode active material layer 11. The positive electrode collector 12 may be any of those commonly used as a positive electrode collector for a battery. The positive electrode collector 12 may be in the form of a foil, a plate, a mesh, a punched metal, a foam, or the like. The positive electrode collector 12 may be made of a metal foil or a metal mesh. In particular, a metal foil is excellent in terms of ease of handling. The positive electrode collector 12 may be made of a plurality of foils. Examples of metals constituting the positive electrode collector 12 include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, and the like. In particular, from the viewpoint of ensuring oxidation resistance, the positive electrode collector 12 may contain Al. The positive electrode collector 12 may have some kind of coating layer on its surface for the purpose of adjusting resistance, or the like. The positive electrode current collector 12 may be a metal foil or a substrate plated or vapor-deposited with the above metal. When the positive electrode current collector 12 is made of a plurality of metal foils, some layer may be present between the plurality of metal foils. The thickness of the positive electrode current collector 12 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less.

[0046] 2.3 Other In addition to the above configuration, the positive electrode 10 may have a general configuration as a positive electrode of a secondary battery. For example, a tab or a terminal. The positive electrode 10 can be manufactured by a known method except for using the above-mentioned first active material and second active material in combination as a positive electrode active material. For example, the positive electrode active material layer 11 can be easily formed by forming a positive electrode mixture containing the above-mentioned various components in a dry or wet manner. The positive electrode active material layer 11 may be formed together with the positive electrode current collector 12 or may be formed separately from the positive electrode current collector 12.

[0047] 3. Lithium-ion secondary battery As shown in FIG. 1, a lithium ion secondary battery 100 according to an embodiment has a positive electrode 10, an electrolyte layer 20, and a negative electrode 30. Here, the positive electrode 10 includes the positive electrode active material of the present disclosure. As described above, the positive electrode active material of the present disclosure has a low diffusion barrier and is excellent in high-speed charging performance, so that a lithium ion secondary battery having the positive electrode active material is likely to have excellent cycle characteristics during high-speed charging and discharging, for example. A specific configuration example of the positive electrode 10 is as described above.

[0048] 3.1 Electrolyte layer The electrolyte layer 20 contains at least an electrolyte. When the lithium ion secondary battery 100 is a solid-state battery (a battery containing a solid electrolyte, which may be a battery partially using a liquid electrolyte in combination, or an all-solid-state battery not containing a liquid electrolyte), the electrolyte layer 20 contains a solid electrolyte and may further contain a binder or the like. In this case, the content of the solid electrolyte and the binder or the like in the electrolyte layer 20 is not particularly limited. On the other hand, when the lithium ion secondary battery 100 is an electrolyte battery, the electrolyte layer 20 contains an electrolyte solution and may further have a separator or the like for holding the electrolyte solution and preventing contact between the positive electrode active material layer 11 and the negative electrode active material layer 31. The thickness of the electrolyte layer 20 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.

[0049] The electrolyte contained in the electrolyte layer 20 may be appropriately selected from those exemplified as electrolytes that may be contained in the positive electrode active material layer described above. The binder that may be contained in the electrolyte layer 20 may also be appropriately selected from those exemplified as binders that may be contained in the positive electrode active material layer described above. The electrolyte and the binder may each be used alone or in combination of two or more. The separator may be any separator that is normally used in lithium ion secondary batteries, and examples of the separator include those made of resins such as polyethylene (PE), polypropylene (PP), polyester, and polyamide. The separator may have a single layer structure or a multi-layer structure. Examples of the multi-layer separator include a separator with a two-layer structure of PE / PP, or a separator with a three-layer structure of PP / PE / PP or PE / PP / PE. The separator may be made of a nonwoven fabric such as a cellulose nonwoven fabric, a resin nonwoven fabric, or a glass fiber nonwoven fabric.

[0050] 3.2 Negative electrode As shown in FIG. 1, the negative electrode 30 may include a negative electrode active material layer 31 and a negative electrode current collector 32.

[0051] 3.2.1 Negative electrode active material layer The negative electrode active material layer 31 includes at least a negative electrode active material, and may further include an electrolyte, a conductive assistant, a binder, and the like. Furthermore, the negative electrode active material layer 31 may further include various additives. The contents of the negative electrode active material, electrolyte, conductive assistant, binder, and the like in the negative electrode active material layer 31 may be appropriately determined according to the intended battery performance. For example, the content of the negative electrode active material may be 40 mass% or more, 50 mass% or more, or 60 mass% or more, and may be 100 mass% or less, or 90 mass% or less, with the entire negative electrode active material layer 31 (total solid content) being 100 mass%. The shape of the negative electrode active material layer 31 is not particularly limited, and may be, for example, a sheet-like negative electrode active material layer having a substantially flat surface. The thickness of the negative electrode active material layer 31 is not particularly limited, and may be, for example, 0.1 μm or more or 1 μm or more, and may be 2 mm or less or 1 mm or less.

[0052] As the negative electrode active material, various materials having a potential (charge / discharge potential) for absorbing and releasing lithium ions that is lower than that of the positive electrode active material having the above-mentioned O2 type structure can be used. For example, silicon-based active materials such as Si, Si alloys, and silicon oxide; carbon-based active materials such as graphite and hard carbon; various oxide-based active materials such as lithium titanate; metallic lithium, lithium alloys, and the like can be used. Only one type of negative electrode active material may be used alone, or two or more types may be used in combination.

[0053] The shape of the negative electrode active material may be any shape that is common for a negative electrode active material of a battery. For example, the negative electrode active material may be in a particulate form. The negative electrode active material particles may be primary particles or secondary particles formed by agglomeration of a plurality of primary particles. The average particle diameter (D50) of the negative electrode active material particles may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less. Alternatively, the negative electrode active material may be in a sheet form (foil form, film form) such as lithium foil. That is, the negative electrode active material layer 31 may be made of a sheet of the negative electrode active material.

[0054] Examples of the electrolyte that can be contained in the negative electrode active material layer 31 include the above-mentioned solid electrolyte, electrolytic solution, or a combination thereof. Examples of the conductive assistant that can be contained in the negative electrode active material layer 31 include the above-mentioned carbon material and metal material. The binder that can be contained in the negative electrode active material layer 31 may be appropriately selected from, for example, those exemplified as the binder that can be contained in the above-mentioned positive electrode active material layer 11. Only one type of electrolyte or binder may be used alone, or two or more types may be used in combination.

[0055] 3.2.2 Negative electrode current collector As shown in FIG. 1, the negative electrode 30 may include a negative electrode current collector 32 in contact with the negative electrode active material layer 31. The negative electrode current collector 32 may be any of those commonly used as a negative electrode current collector for a battery. The negative electrode current collector 32 may be in the form of a foil, a plate, a mesh, a punched metal, a foam, or the like. The negative electrode current collector 32 may be a metal foil or a metal mesh, or may be a carbon sheet. In particular, a metal foil is excellent in terms of ease of handling. The negative electrode current collector 32 may be made of a plurality of foils or sheets. Examples of metals constituting the negative electrode current collector 32 include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, and the like. In particular, from the viewpoint of ensuring reduction resistance and being difficult to alloy with lithium, the negative electrode current collector 32 may contain at least one metal selected from Cu, Ni, and stainless steel. The negative electrode current collector 32 may have some kind of coating layer on its surface for the purpose of adjusting the resistance or the like. The negative electrode current collector 32 may be a metal foil or a base material on which the above metal is plated or vapor-deposited. When the negative electrode current collector 32 is made of a plurality of metal foils, some kind of layer may be present between the plurality of metal foils. The thickness of the negative electrode current collector 32 is not particularly limited. For example, it may be 0.1 μm or more or 1 μm or more, and may be 1 mm or less or 100 μm or less.

[0056] 3.3 Other matters The lithium ion secondary battery 100 may have the above-mentioned components housed inside an exterior body. Any known exterior body for a battery can be used as the exterior body. A plurality of batteries 100 may be electrically connected and stacked in any manner to form an assembled battery. In this case, the assembled battery may be housed inside a known battery case. The lithium ion secondary battery 100 may also have other obvious components such as necessary terminals. The shape of the lithium ion secondary battery 100 may be, for example, a coin type, a laminate type, a cylindrical type, a square type, or the like.

[0057] The lithium ion secondary battery 100 can be manufactured by applying a known method. For example, it can be manufactured as follows. However, the manufacturing method of the lithium ion secondary battery 100 is not limited to the following method, and each layer may be formed by, for example, dry molding or the like. (1) The negative electrode active material constituting the negative electrode active material layer is dispersed in a solvent to obtain a negative electrode layer slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used, and N-methylpyrrolidone (NMP) can also be used. The negative electrode layer slurry is then applied to the surface of a negative electrode current collector using a doctor blade or the like, and then dried to form a negative electrode active material layer on the surface of the negative electrode current collector, forming a negative electrode. (2) The positive electrode active material constituting the positive electrode active material layer is dispersed in a solvent to obtain a positive electrode layer slurry. The solvent used in this case is not particularly limited, and water or various organic solvents can be used, and N-methylpyrrolidone (NMP) can also be used. The positive electrode layer slurry is applied to the surface of a positive electrode current collector using a doctor blade or the like, and then dried to form a positive electrode active material layer on the surface of the positive electrode current collector, which serves as a positive electrode. (3) The layers are laminated so that the electrolyte layer (solid electrolyte layer or separator) is sandwiched between the negative electrode and the positive electrode to obtain a laminate having the negative electrode current collector, the negative electrode active material layer, the electrolyte layer, the positive electrode active material layer, and the positive electrode current collector in this order. Other members such as terminals are attached to the laminate as necessary. (4) The laminate is housed in a battery case, and in the case of an electrolyte battery, the battery case is filled with electrolyte, and the laminate is immersed in the electrolyte and sealed in the battery case to form a secondary battery. In the case of an electrolyte battery, the electrolyte may be impregnated in the negative electrode active material layer, the separator, and the positive electrode active material layer at the above step (3).

[0058] 4. Manufacturing method of positive electrode active material The positive electrode active material of the present disclosure can be produced, for example, by the following method. That is, the method for producing the positive electrode active material of the present disclosure includes: Obtaining a Na compound having a P2 type structure, and by ion exchange, replacing at least a portion of the Na in the Na compound with Li to obtain a Li compound having an O2 type structure; Includes.

[0059] 4.1 Synthesis of sodium compounds with P2 structure Since the O2 type structure is a metastable phase, it is necessary to first synthesize a Na compound having a similar P2 type structure, and then ion-exchange at least a part of the Na of the Na compound with Li to obtain the O2 type structure. For example, in the manufacturing method of the present disclosure, a Na compound having a P2 type structure and containing the element M as a constituent element is first obtained. A Na compound having a P2 type structure and containing the element M as a constituent element can be synthesized by applying a known method. For example, a Na source is further mixed with a precipitate derived from an ion source capable of forming a precipitate in an aqueous solution with a transition metal ion, a transition metal source containing at least one of Mn, Ni, and Co, and an M source containing at least one of B, Mg, Al, K, Ca, Ti, Cr, Ga, Zr, Nb, and Mo to obtain a mixture, and the mixture is optionally molded and pre-fired, and then fired, thereby synthesizing a Na compound having a P2 type structure.

[0060] Examples of the ion source capable of forming a precipitate with the transition metal ion include salts such as carbonates and nitrates, sodium hydroxide, and sodium oxide. Examples of the transition metal source and M source include salts such as nitrates, sulfates, and carbonates, and hydroxides. The ion source, the transition metal source, and the M source may be prepared as solutions, and then the solutions may be dropped and mixed to obtain a precipitate. The transition metal source and the M source may be prepared as separate solutions, or may be prepared as the same solution. When obtaining a precipitate, various sodium compounds may be used as a base, and an aqueous ammonia solution or the like may be added to adjust the basicity. The amount of the Na source mixed before the calcination of the precipitate may be determined taking into account the amount of Na lost during the calcination. The pre-calcination is performed at a temperature equal to or lower than the main calcination. The pre-calcination may be omitted. The main calcination may be performed at a temperature of, for example, 700°C to 1100°C. The temperature is preferably 800°C to 1000°C. If the firing temperature is too low, Na doping is not performed, and if the firing temperature is too high, the O3 type structure is likely to be formed instead of the P2 type structure. The firing atmosphere is not particularly limited, and may be, for example, an oxygen-containing atmosphere such as air atmosphere or an inert gas atmosphere.

[0061] 4.2 Ion exchange In the manufacturing method of the present disclosure, at least a part of Na in the above Na compound is replaced with Li by ion exchange to obtain a Li compound having an O2 type structure. Ion exchange can be performed using an aqueous solution containing lithium halide or a molten salt of lithium halide and other lithium salt. From the viewpoint that the P2 type structure is easily broken by the intrusion of water and from the viewpoint of crystallinity, the method using the molten salt is preferable among the above two methods. That is, by mixing the above Na compound having the P2 type structure with the molten salt and heating it to a temperature equal to or higher than the melting point of the molten salt, at least a part of Na in the Na compound can be replaced with Li by ion exchange.

[0062] The lithium halide constituting the molten salt is preferably at least one of lithium chloride, lithium bromide, and lithium iodide. The other lithium salt constituting the molten salt is preferably lithium nitrate. By using the molten salt, the melting point becomes lower than when the lithium halide or other lithium salt is used alone, and ion exchange can be performed at a lower temperature. In the molten salt, the mixture ratio of the lithium halide and other lithium salt is not particularly limited.

[0063] The temperature in the ion exchange may be, for example, 600°C or less, 500°C or less, 400°C or less, or 350°C or less, and may be room temperature or more or 100°C or more. If the temperature in the ion exchange is too high, the stable phase O3 type structure is likely to be generated instead of the O2 type structure. When an aqueous solution containing lithium halide is used, the ion exchange is possible even at room temperature. On the other hand, when a molten salt is used, the ion exchange is performed at a temperature equal to or higher than the melting point of the molten salt, as described above. From the viewpoint of shortening the time required for the ion exchange, the temperature in the ion exchange may be 100°C or more. EXAMPLES

[0064] The technology of the present disclosure will be described in more detail below with reference to examples, but the technology of the present disclosure is not limited to the following examples.

[0065] 1. Example 1 1.1 Synthesis of sodium compounds with P2 structure Mn(NO3)2·6H2O, Ni(NO3)2·6H2O, Co(NO3)2·6H2O, and Al(NO3)3·9H2O were used as raw materials and dissolved in pure water so that the molar ratio of Mn, Ni, Co, and Al was 5:2:2:1. Meanwhile, a Na2CO3 solution with a concentration of 12 wt% was prepared, and these two solutions were simultaneously dropped into a beaker. At this time, the titration speed was controlled so that the pH was 7.0 or more and less than 7.1. After the titration was completed, the mixed solution was stirred at 50°C and 300 rpm for 24 hours. The obtained reaction product was washed with pure water, and only the precipitated powder was separated by centrifugation. The obtained powder was dried at 120°C for 48 hours and then crushed in an agate mortar to obtain a powder. Na2CO3 was added to the obtained powder, and ... 0.75 Mn 0.5 Ni 0.2 Co 0.2 Al 0.1 The mixture was mixed so that the mixture would be O2. The mixed powder was pressed under a load of 2 tons using cold isostatic pressing to produce pellets. The resulting pellets were pre-fired in air at 600°C for 6 hours, and then fired at 900°C for 24 hours to synthesize a Na compound with a P2 type structure.

[0066] 1.2 Ion exchange LiNO3 and LiCl were mixed in a mass ratio of 88:12, and weighed out so that the molar ratio of Li was 10 times that of the Na compound with a P2 type structure. The Na compound was mixed with the LiNO3·LiCl mixed powder, and ion exchange was carried out at 280°C for 1 hour in an air atmosphere. After the ion exchange, water was added to dissolve the excess salt, and the mixture was washed with water to obtain a positive electrode active material with an O2 type structure.

[0067] 1.3 Preparation of the positive electrode 85 g of the positive electrode active material obtained as described above and 10 g of carbon black as a conductive additive were uniformly mixed in 125 mL of n-methylpyrrolidone solution in which 5 g of PVdF was dissolved as a binder, to prepare a positive electrode composite paste. This paste was applied to an Al current collector with a thickness of 15 μm in a basis weight of 6 mg / cm. 2The laminate was then pressed to a paste thickness of 45 μm and a paste density of 2.4 g / cm. 3 Finally, this laminate was cut to a diameter of 16 mm to obtain a positive electrode.

[0068] 1.4 Preparation of the negative electrode The Li foil was cut to a diameter of 19 mm to obtain a negative electrode.

[0069] 1.5 Preparation of lithium-ion secondary battery A CR2032 coin cell was fabricated using the obtained positive and negative electrodes. A PP porous separator was used as the separator, and the electrolyte was a mixture of EC (ethylene carbonate) and DMC (dimethyl carbonate) in a volume ratio of 3:7, with lithium hexafluorophosphate (LiPF6) dissolved at a concentration of 1 mol / L as the supporting electrolyte.

[0070] 2. Example 2 A positive electrode active material and a lithium ion secondary battery were obtained in the same manner as in Example 1, except that Mg(NO3)2·6H2O was used instead of Al(NO3)3·9H2O, and a Na compound having a P2 type structure was synthesized with a molar ratio of Mn, Ni, Co and Mg of 10:3:6:1.

[0071] 3. Comparative Example 1 A positive electrode active material and a lithium ion secondary battery were obtained in the same manner as in Example 1, except that a Na compound having a P2 type structure was synthesized by using no Al(NO3)3·9H2O and by adjusting the molar ratio of Mn, Ni and Co to 5:2:3.

[0072] 4. Evaluation 4.1 Identification of crystalline phases by XRD The crystal phase of each of the positive electrode active materials obtained in Examples 1 and 2 and Comparative Example 1 was identified by powder X-ray diffraction. The results are shown in Figure 2. As shown in Figure 2, each of the positive electrode active materials had an O2 type structure (and its derived structure).

[0073] 4.2 Identification of composition by ICP-AES ICP-AES measurements were performed on each of the positive electrode active materials obtained in Examples 1 and 2 and Comparative Example 1. The results are shown in Table 1 below. The compositions shown in Table 1 below are standardized so that the sum of the compositions of Mn, Ni, Co, Al, and Mg is 1.00. As shown in Table 1, it can be seen that the target composition was obtained for each positive electrode active material.

[0074] [Table 1]

[0075] 4.3 Analysis by XPS The surfaces of the positive electrode active materials obtained in Examples 1 and 2 and Comparative Example 1 were analyzed by XPS. FIG. 3 shows XPS spectra at 0 to 9 eV. Table 2 below shows the ratio I1 / I2 of the maximum peak intensity I1 of peak 1 present at 2 eV or less and the maximum peak intensity I2 of peak 2 present at more than 2 eV and 8 eV or less for each positive electrode active material. As shown in FIG. 3 and Table 2, in both Examples 1 and 2 and Comparative Example 1, a peak 1 derived from a transition metal was confirmed at 2 eV or less. In addition, in Examples 1 and 2, a large peak 2 exists in the range of binding energy of 2 to 6 eV, whereas in Comparative Example 1, a peak 2 exists in the range of binding energy of 6 to 8 eV, and no peak was confirmed in the range of binding energy of 2 to 6 eV. In Comparative Example 1, the peak 2A derived from oxygen appears as it is as peak 2. In contrast, in Examples 1 and 2, it is considered that the peak 2A derived from oxygen is mixed with the peak 2B derived from Al or Mg to become the large peak 2.

[0076] [Table 2]

[0077] 4.4 Evaluation of charge / discharge cycle characteristics Each of the lithium ion secondary batteries prepared in Examples 1 and 2 and Comparative Example 1 was charged and discharged at a charge / discharge rate of 0.1C, and the initial discharge capacity was measured. Thereafter, the charge / discharge rate was gradually increased to 0.5C, 1C, and 5C, and the discharge capacity at each rate was measured, and the ratio to the initial discharge capacity was calculated. It can be said that the larger the ratio, the better the cycle characteristics are. In the charge / discharge, charging was performed up to 4.8V, and discharging was performed up to 2.0V. The results are shown in Table 3 below. As shown in Table 3 below, the lithium ion secondary batteries according to Examples 1 and 2 can ensure high charge / discharge capacity during high-speed charging / discharging, and have high cycle characteristics, compared to the lithium ion secondary battery according to Comparative Example 1.

[0078] [Table 3]

[0079] The reason why the cycle characteristics during high-rate charge and discharge in Examples 1 and 2 are improved compared to Comparative Example 1 is considered to be as follows. That is, as in Comparative Example 1, the positive electrode active material having an O2 type structure is prone to valence localization and has a high diffusion barrier. When the valence is localized and the diffusion barrier is high, it has a negative effect on high-rate charge and discharge performance. In contrast, in Examples 1 and 2, since Al and Mg, which have a large electron spread, are introduced into the O2 type structure, the valence is delocalized, the electrons are easily separated from the atoms and spread, the diffusion barrier is lowered, and the cycle characteristics during high-rate charge and discharge are improved. This is also clear from the measurement results of the valence band by XPS shown in FIG. 3.

[0080] 5. Supplementary Information In the above, a positive electrode active material having a specific composition and containing Al or Mg as the additive element M is exemplified, but the technology of the present disclosure is not limited to this form. As long as it has an O2 type structure, it is considered that a composition other than the above-mentioned can have the same effect, and it is also considered that, in addition to Al and Mg, for example, B, K, Ca, Ti, Cr, Ga, Zr, Nb, and Mo can also have the same effect due to the above-mentioned mechanism as the additive element. [Explanation of symbols]

[0081] 10 positive electrode 11 Cathode active material layer 12 Positive electrode current collector 20 Electrolyte layer 30 negative electrode 31 Negative electrode active material layer 32 Negative electrode current collector 100 Secondary battery

Claims

1. A positive electrode active material having an O2 type structure, Constituent elements include at least Li, Mn, Ni, Co, M, and O, The M is at least one of Mg and Al; Li a Na b Mn x-p Ni y-q Co z-r M p+q+r O 2 (where: 0<a≦1, 0≦b≦0.05, 0.3≦x≦0.7, 0.1≦y≦0.3, 0.2≦z≦0.5, x+y+z=1, and 0.05≦p+q+r≦0.14 (The relationship is fulfilled.) Having a composition represented by Cathode active material.

2. When the surface of the positive electrode active material is analyzed by X-ray photoelectron spectroscopy (XPS), the maximum peak intensity I 1 and the maximum peak intensity I of peak 2 existing between 2 eV and 8 eV 2 Comparison with I 1 / I 2 is 0.5 or more and 1.2 or less, The positive electrode active material according to claim 1 .

3. The peak 2 exists at more than 2 eV and less than 6 eV. The positive electrode active material according to claim 2 .

4. A lithium ion secondary battery having a positive electrode, an electrolyte layer, and a negative electrode, The positive electrode comprises the positive electrode active material according to any one of claims 1 to 3. Lithium-ion secondary battery.

Citation Information

Patent Citations

  • Method for producing positive electrode active material and method for manufacturing lithium ion battery

    JP2021068555A

  • Method for producing positive electrode active material and method for manufacturing lithium ion battery

    JP2021068556A

  • Positive electrode active material for nonaqueous electrolyte secondary batteries and method for producing same

    WO2015049796A1